Construction of PZT-5H mechano-electric model based on strain rate dependence and its numerical simulation in overload igniter application. (June 2021) - Wang, Ruizhi; Tang, Enling; Yang, Guolai; Sun, Quanzhao; Han, Yafei; Chen, Chuang
Abstract: Although the force-electricity relationship of piezoelectric ceramics under pulse stress is found to be nonlinear, there is still lacking a reliable model describing this relationship. To bridge this research gap, the mechanical and electrical responses of PZT-5H (Pb1·0 [Zr0·49 Ti0·46 (Nb0·25 Sb0.75 )0.05 ]1.0 O3 ) under different strain rates were investigated through uniaxial compression tests and split-Hopkinson pressure bar (SHPB) experiments with an additional electrical output measurement system. With reference to the nonlinear viscoelastic constitutive equation and the piezoelectric equation, a PZT-5H mechano-electric model considering the strain rate effects was built based on the experimental data. The incremental form of the mechano-electric model was established based on the Piola-Kirchhoff stress tensor and Green strain tensor theory. The model was numerically simulated with a user-defined material subroutine in the explicit finite element software ABAQUS. The accuracy of the material subroutine was verified with finite element models of the uniaxial quasi-static compression and the high strain rate SHPB tests. The finite element simulation results were verified with the experimental results, and the two agreed well. The material subroutine was then adopted to predict the mechanical and electrical response of the piezoelectric ceramics inside the overload igniter during projectile launch and impact. The analysis results show that the overload igniter can be stably activated within 200 μs under the launch overload and successfully ignited within 5 μs at speed as low as 50 m/s under the impact overload. Highlights: A PZT-5H mechano-electric model considering the strain rate effect is established. By establishing a user-defined material subroutine in the ABAQUS/Explicit, the model was numerically realized. The models of uniaxial quasi-static compression and SHPB were established to verify the accuracy of the material subroutine. This subroutine predict the mechano- electric response of the piezoelectric ceramics inside the overload igniter during the projectile launching and impacting target.